Manipulating intrinsic behaviors of graphene by substituting alkaline earth metal atoms in its structure. Issue 27 (14th March 2017) - Rafique, Muhammad; Shuai, Yong; Tan, He-Ping; Hassan, Muhammad
Abstract : In this paper, the structural, electronic, magnetic and optical properties of alkaline earth metal (AEM) atom-doped monolayer graphene are investigated using first-principles calculations. Abstract : In this paper, the structural, electronic, magnetic and optical properties of alkaline earth metal (AEM) atom-doped monolayer graphene are investigated using first-principles calculations. It is found that, Be, Mg and Ca atom substituted graphene structures exhibit half metallic behavior with 0.00 μ B, 1.86 μ B, and 4.00 μ B magnetic moments, respectively. While, Sr and Ba atom-doped graphene structures display indirect band gap semiconductor behavior with 3.16 μ B and 0.46 μ B magnetic moments, respectively. All the impurity atoms are tightly bonded with graphene, having significant formation energy and the direction of charge transfer is from AEM atoms to the graphene. Upon analyzing density of states plots we found that the s and p orbitals of impurity atoms give rise to magnetic moments in graphene complexes. The optical properties for pure graphene and AEM atom-doped graphene complexes have been calculated within the random phase approximation (RPA) approach. The absorption coefficient and reflectivity plots for doped graphene complexes are calculated and compared to the results obtained for pure graphene. A significant change in optical properties specifically in the absorption spectrum of graphene is obtained after AEM atom substitution. It is found that AEM atom substitution into graphene produces an increase in the absorption spectrum in the energy range of 0 to 3 eV and a reduction in absorption peaks at a 14 eV energy level. In addition, a third minimum absorption peak appears in the energy interval of 7 to 11 eV, which is not present in the absorption spectrum of pure graphene. A significant red shift in absorption towards the visible range of radiation is also obtained. An increase in reflectivity peak in the low energy region is observed after AEM atom substitution into graphene. We believe that our results are suitable for further experimental exploration and useful for graphene based spintronic and optoelectronic devices.